Analisis Komunikasi dan Budaya Organisasi terhadap Kinerja Karyawan pada Perusahaan PT Kereta Api Indonesia (Persero) - Rismawati Rismawati; Anggi Maulana; Shavira Nafa Dilla; Supriyanto Supriyanto; Siti Nuraini (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to analyze the application of Organizational Theory at PT Kereta Api Indonesia (Persero) in the context of organizational communication, organizational culture and employee performance. PT Kereta Api Indonesia as a state-owned company engaged in the transportation sector has unique challenges and opportunities in managing its human resources and operations. Through a qualitative approach, this study collected data from interviews with managers and employees, as well as analysis of internal company documents. The results of this study indicate that effective communication and a strong organizational culture contribute significantly to improving employee performance. In addition, the implementation of clear organizational values ​​and ongoing training are key factors in creating a productive work environment. This study is expected to provide insight for PT Kereta Api Indonesia management in optimizing organizational strategies to achieve better company goals.